Form for reporting Iowa Christmas bird counts to Iowa Bird Life, Mina Landes, January 3, 1988 - Landes, Minaet al (1988)
Iowa Christmas bird counts of regular and uncommon species found in Fort Dodge contributed by Mina Landes, January 3, 1988. This item was used as supporting documentation for the Iowa Ornithologists Union Quarterly field report of winter 1987-1988. Epson - sheet feed